Strategic Management Model For Government Agency Performance Accountability System Of Bekasi Regency, West Java Province - Mutiara Salsabila; Sadu Wasistiono; Yudi Rusfiana (Sean Institute, 2024)
In the 2020-2022 period, the achievement of the Government Agency Performance Accountability System (SAKIP) of Bekasi Regency, West Java, has not been optimal. This is due to SAKIP not being a Key Performance Indicator (KPI) in the 2017-2022 Regional Medium-Term Development Plan (RPJMD). As a result, programs, activities, and budgets do not support the achievement of SAKIP. This research uses the strategic management theory of Wheelen Hunger (2012), including: Environmental Scanning (external opportunities and threats, internal strengths and weaknesses), Strategy Formulation (mission, goals, strategies, policies), Strategy Implementation (programs, budgets, procedures ), and Evaluation and Control (performance). This research was conducted using qualitative methods and deductive analysis, utilizing interview data, documents, and statistics. The results show that strategic management in Bekasi Regency has not been optimal, especially in the aspect of Environmental Scanning which has not been given enough attention. In addition, strategy formulation, implementation, control, and evaluation are still weak. To optimize the strategic management of SAKIP, regular evaluation is needed through a continuous strategic management model that includes all stages of strategic management. Strengthening leadership, political and budgetary commitment to strategy formulation, implementation and evaluation is key. This optimization involves applying the updated Wheelen Hunger-based strategic model as needed.